Brain-computer interface - Shrama S.J.; Gupta R. (My University, 2025)
Innovative technologies called brain-computer interfaces (BCIs) create a nonstop line of communication between the brain and other objects. They have a great deal of promise to improve human capacities, provide people with motor disabilities control over assistive technology, and open up new channels for communication and engagement. This abstract provides an overview of BCIs, their underlying principles, and their applications across various domains, including healthcare, rehabilitation, and human-computer interaction. It also highlights the challenges and future directions in BCI research, such as improving signal processing techniques, enhancing system usability, and addressing ethical considerations. With ongoing advancements in technology and our understanding of the brain, BCIs are poised to revolutionize the way we interact with machines and augment human abilities. © 2025 Elsevier Inc. All rights reserved.